The value of intra-abdominal pressure monitoring through transvesical route in the choice and outcome of management of congenital abdominal wall defects. Issue 2 (April 2017) - Elsaied, Adham; Medhat, Sherif; Sheir, Hesham; Aly, Kamal
Abstract : Introduction: Gastroschisis and omphalocele are most common congenital abdominal wall defects (AWDs). Surgical management aims to reduce the evisceration safely, close the defect with a cosmetically acceptable outcome under guidance of intraoperative monitoring of intra-abdominal pressure (IAP). Intravesical pressure monitoring technique recommended by (WSACS) is the most reliable technique for IAP measurement in neonates. Aim: The aim of this study is to assess the value of IAP monitoring via vesical pressure measurement in the choice and outcome of management of congenital AWDs. Patients and methods: This is a prospective study of 25 cases that suffered congenital anterior AWDs (gastroschisis and omphalocele) admitted to Mansoura University Children Hospital during the period from October 2013 to October 2015. They were all operated upon guided by IVP monitoring during and after repair. Results: In our study, 14 (56%) cases presented with gastroschisis and 11 (44%) presented with exomphalos with a median age of 24 h. Males (56%) were slightly more than females (44%). Congenital anomalies were reported in 16 cases (64%). Primary fascial closure was successful in 15 (60%) cases, whereas Silo repair was done in six (24%) cases and skin closure in only four (16%) cases. During the attempts of closure the mean abdominal perfusion pressure was 40.24±5.59, the mean peak inspiratory pressure was 24±6.11 and the mean IAP was 22.60±6.89. Two cases developed intra-abdominal hypertension after abdominal closure (8%) and only one of them needed decompressive laparotomy (4%). Postoperative complications were reported in 15 (60%) cases and mortality occurred in eight (32%) cases. Conclusion: Increased IAP secondary to forceful closure of the abdominal defect is associated with the occurrence of complications. IVP monitoring is feasible during closure of AWDs and a threshold of 20 cm H2 O is appropriate to decide between primary and staged approach.